Pengaruh CEO Narcissism Terhadap Manajemen Laba dengan Koneksi Politik Sebagai Variabel Moderasi - Saputra, Muhammad Bayu; Primasari, Dona (LPPM Institut Pendidikan Nusantara Global, 2024)
The primary objective of this research is to obtain empirical evidence regarding the impact of CEO narcissism on earnings management, taking into account political connections as a moderating factor. The study focuses on state-owned enterprises listed on the Indonesia Stock Exchange during the period 2017-2021. The selection of samples in this study utilizes purposive sampling, yielding a sample size of 15 state-owned companies. The analytical approach involves multiple linear regression. The findings suggest that: (1) CEO narcissism positively influences earnings management, and (2) the presence of political connections as a moderating variable does not significantly alter the impact of CEO narcissism on earnings management.